Development and Validation of a Sensitive HPLC-MS/MS-ESI Method for Determination of Febuxostat: Application to Pharmacokinetic Study - Choudhury, Hira; Gorain, Bapi; Das, Ayan; Ghosh, Balaram; Pal, Tapan (Current Analytical Chemistry, 2014)
A simple, novel and sensitive assay method was developed and validated for the estimation of febuxostat, an anti-gout agent, in human plasma using high-performance liquid chromatography coupled to tandem mass spectrometry. The bioanalytical method is involved in liquid–liquid extraction of febuxostat and rosiglitazone (internal standard: IS) using micro volume (100 μL) human plasma and quantitation by triple quadrupole mass spectrometry with the help of electrospray ionization technique, operating in multiple reaction monitoring and positive ion modes. Chromatographic separation was achieved using an isocratic mobile phase (0.2% formic acid solution in water : methanol, 10:90, v/v) at a flowrate of 0.5 mL/min on a ZORBAX SB-CN column (50x4.6 mm, 3.5 m) with a total run time of 2.2 minutes. The MS/MS ion transitions were monitored as 317.3→261.1 for febuxostat and 358.3→135.2 for IS. Method validation was examined as per FDA guidelines and the results obtained were quite satisfactory. The lower limit of quantitation obtained was 0.005 μg/mL and the linearity range reported an extension from 0.005 to 10 μg/mL. Febuxostat was found to be stable in a battery of stability studies viz. bench-top, auto-sampler, freeze thaw cycle and long-term. The method was proved highly reproducible with low chromatographic retention cycle and was successfully applied to quantitatively assess febuxostat in human plasma obtained from the pharmacokinetic study.
Keywords: febuxostat